New World leishmaniasis from Spain. Issue 926 (1st December 2002) - Tomson, N; Symonds, R P; Moir, A A; Kendall, C H; Wiselka, M J
Abstract : A 69 year old man living in Spain contracted mucocutaneous leishmaniasis involving the nose. The infecting organism was Leishmania infantum, which only rarely causes the New World form of the disease. The source of infection was probably a neighbour's dog. The patient began treatment with liposomal amphotericin B but died of pneumonia two months later.